2022
DOI: 10.2460/javma.20.09.0534
|View full text |Cite
|
Sign up to set email alerts
|

Complications, prognostic factors, and long-term outcomes for dogs with brachycephalic obstructive airway syndrome that underwent H-pharyngoplasty and ala-vestibuloplasty: 423 cases (2011–2017)

Abstract: OBJECTIVE To describe the H-pharyngoplasty procedure, report the outcomes of dogs with brachycephalic obstructive airway syndrome (BOAS) treated with ala-vestibuloplasty and H-pharyngoplasty with a CO2 laser, and identify prognostic factors. ANIMALS 423 dogs. PROCEDURES Medical records of dogs admitted for BOAS from 2011 to 2017 were reviewed. Dogs were included if they were treated with ala-vestibuloplasty and H-pharyngoplasty with a CO2 laser. Signalment, physical examination findings, grades at admissio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 27 publications
3
6
0
Order By: Relevance
“…Aspiration pneumonia is a common complication in brachycephalic dogs due to their increased risk of regurgitation. The rate of postoperative aspiration pneumonia in the current study was similar to previously reported rates that ranged from 1% to 7% (Carabalona et al., 2022; Costa et al., 2020; Fenner et al., 2020; Lindsay et al., 2020; Stordalen et al., 2020). Although the association of BCS with the development of this complication was not maintained in the multivariable regression model, it is still reasonable to recommend weight loss to overweight dogs before proceeding to airway surgery despite previous reports suggesting a decrease in complication rates with increased bodyweight (Gruenheid et al., 2018).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Aspiration pneumonia is a common complication in brachycephalic dogs due to their increased risk of regurgitation. The rate of postoperative aspiration pneumonia in the current study was similar to previously reported rates that ranged from 1% to 7% (Carabalona et al., 2022; Costa et al., 2020; Fenner et al., 2020; Lindsay et al., 2020; Stordalen et al., 2020). Although the association of BCS with the development of this complication was not maintained in the multivariable regression model, it is still reasonable to recommend weight loss to overweight dogs before proceeding to airway surgery despite previous reports suggesting a decrease in complication rates with increased bodyweight (Gruenheid et al., 2018).…”
Section: Discussionsupporting
confidence: 91%
“…The results of this study highlight the prevalence and risk factors of postoperative respiratory complications following multilevel BOAS surgery. The proportion of dogs experiencing at least one postoperative complication was 15% which falls within the range of previously reported rates (3.2% to 26%) (Carabalona et al., 2022; Fasanella et al., 2010; Poncet et al., 2006; Riecks et al., 2007). Airway obstruction is a potentially fatal complication following BOAS surgery.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…This suggests either that standard corrective surgery does not reduce upper airway resistance adequately to prevent collapse, or that there may be inadequate upper airway dilator muscle function in some brachycephalic dogs. Larger studies on the effect of traditional surgical correction, modified multilevel surgery, 64 and H‐pharyngoplasty surgery 68 on this condition are warranted.…”
Section: Discussionmentioning
confidence: 99%
“…4,9 However, increasing age was a risk factor for death in a more recent study of 423 brachycephalic dogs undergoing BOAS surgery. 10 Brachycephalic dogs were reportedly four times more likely to experience postanesthetic complications compared to nonbrachycephalic dogs, and prolonged anesthesia was a risk factor for development of complications including aspiration pneumonia and need for temporary tracheostomy. 9,11 Also, young brachycephalic dogs with normal body condition and presence of laryngeal collapse undergoing traditional multilevel surgery for BOAS seemed to have less favorable postoperative prognosis.…”
Section: Introductionmentioning
confidence: 98%